1970
DOI: 10.1039/tf9706602579
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the activation volume of a Diels-Alder reaction

Abstract: The kinetics of the isoprene+maleic anhydride reaction have been studied in various solvents at pressures up to 1400 atm. The solvent effect on the activation volumes and energies at 35°C are reported. It is shown how the solvent effect on activation volumes is useful both for mechanistic interpretation as well as for determination of the dipole moment of the transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…For this reaction in other solvents it was found that V = retro < 0 and V = forw / V r-n > 1 [11,31]. In the DAR with maleic anhydride, the "normal" relationship V = retro > 0 and V = forw / V r-n < 1 in acetonitrile and ethyl acetate, and the "abnormal" relationship in other solvents V = retro < 0 and V = forw / V r-n > 1, were obtained [18][19][20]. Different solvent accessibility is the reason for the large differences in the values of PMV of branched structures of adamantane (136.9 and 142.7) and congressane (160.2 and 177.4 cm 3 ·mol −1 ) in n-hexane and benzene [32].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…For this reaction in other solvents it was found that V = retro < 0 and V = forw / V r-n > 1 [11,31]. In the DAR with maleic anhydride, the "normal" relationship V = retro > 0 and V = forw / V r-n < 1 in acetonitrile and ethyl acetate, and the "abnormal" relationship in other solvents V = retro < 0 and V = forw / V r-n > 1, were obtained [18][19][20]. Different solvent accessibility is the reason for the large differences in the values of PMV of branched structures of adamantane (136.9 and 142.7) and congressane (160.2 and 177.4 cm 3 ·mol −1 ) in n-hexane and benzene [32].…”
Section: Resultsmentioning
confidence: 93%
“…There are only a few direct measurements of the pressure influence on the rate of adduct decomposition [8,[15][16][17]. Why the AC in isopolar DAR should be more compact than the cycloadduct is not yet understood [15][16][17][18][19][20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of the injection port of a commercial gas chromatograph enabled it to be used as a microreactor suitable for catalyst studies a t temperatures as high as 400 "C (666). Other kinetic studies include the direct determination of the kinetics of gas phase thermolysis reactions (669), measurement of the rate of reversible adsorption of hydrogen on a nickel catalyst (846), study of solvent effects on the activation volume of the Diels-Alder reaction of isoprene and maleic anhydride at pressures up to 1400 atmospheres (379), and evaluation of the rate constant and activation energy for decomposition of IBR in the Brz-IBr-12 system (429).…”
Section: Physical-analytical Measurementsmentioning
confidence: 99%
“…Solvent electrostriction in this reaction can be neglected due to the small effect of solvent polarity on the enthalpy of activation (∆ H ≠ av = 52 ± 2 kJ mol −1 ), the volume of activation (∆ V ≠ av. = –38.5 ± 1.0 cm 3 mol −1 ), and the reaction volume (∆ V r‐n, av = –35.5 ± 1.0 cm 3 mol −1 ) . The “abnormal” ratio of ∆ V ≠ /∆ V r‐n > 1 corresponds to the higher volume compactness of the activated complex with incomplete bond formation as compared to the adduct where bond formation is entirely completed.…”
Section: Introductionmentioning
confidence: 99%